Paradigm shifts in ancient kingship traditions in Tonga : a historical and anthropological examination of political practices and changes throughout the bipartite and tripartite systems of government 1550-1875 AD : the case of Hau : a thesis submitted for the degree of Doctor of Philosophy in Social Anthropology at Massey University (Albany Campus – Auckland) New Zealand - Ilaiu, Siaosi Leini (Massey University, 2019)
This study of traditional Tongan kingship system focuses on the emergence of the hau authority and redesigned of the political history of this ancient society. The main purpose is to take a close look at key elements such as governorship, secular ruler, absolute sovereign, victor, champion or military skills etc, which propounded by competing views that have contributed or responsible for clouding the role and responsibilities of the hau in relation to the rise of the second and third divine dynasties of the Tu’i Ha’atakalaua and the Tu’i Kanokupolu. It is central to this work to rethink the information transmitted by oral tradition by assessing what is said about the origin and designation of the hau office. The purpose therefore is primarily to interpret in light of new evidence the positions of both oral tradition and academic revisionists, and to unveil some material that seems to be missing from the dialogue thus far on the hau. This work aims at restoring some sense of historicity to the understanding of traditional kingship in pre-European Tonga. The study examines the creation of the secular office of the hau, why there was the need to implement such a political development, and the recent debate amongst historians and anthropologists on the issue of ‘what is hau’. The debate started from a challenge on the orthodox version that stated the hau was a secular office created by the TT to take over the executive responsibility in about 1350 AD. A leading Pacific historian Niel Gunson argues that there was a system existed way before this date in which the TT title was open for challenge as a rule by a member of his peers. This idea was disputed in 1982 by another Pacific historian Ian Campbell who argues that there was no set rule for such challenge, it was instead a matter of having the means and opportunity. The study responds to the debate by arguing that there were paradigm shifts in the political history of Tonga that historians and anthropologists have been overlooking and as a consequence have misinterpreted, prolonging the dialogue needlessly. In the light of some new findings, I identify three-paradigm shifts that took place between 1350 AD and 1875 AD. It is the dynamism within this 500-year period that this thesis strives to resuscitate.
Keywords: Tonga; Politics and government; Kings and rulers; History; 451304 Pacific Peoples cultural history; 440107 Social and cultural anthropology